Investigating the efficacy and underlying mechanism of cardioprotection afforded by rooibos (aspalathus linearis) in angiotensin-ii induced cardiac hypertrophy & apoptosis - Sithelo, Pamela (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.